FROM THE EDITOR - Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
The editors of Scientia Militaria are proud to present the second edition of 2009 to its readers. This edition is printed with the financial support of the Netherlands Defence Staff (as reflected on the back cover) and we wish to recognise the support to the journal of Commander Bruno Gerrits, defence attaché at the Royal Netherlands Embassy in South Africa.